Biodegradable Compatibilized Poly(l-lactide)/Thermoplastic Polyurethane Blends: Design, Preparation and Property Testing - Kanyarat Suthapakti (2018)
© 2017, Springer Science+Business Media, LLC. Biodegradable blends of poly(l-lactide) (PLL) toughened with a polycaprolactone-based thermoplastic polyurethane (TPU) elastomer and compatibilized with a purpose-designed poly(l-lactide-co-caprolactone) (PLLCL) copolymer were prepared. Both 2-component (PLL/TPU) and 3-component (PLL/TPU/PLLCL) blends of various compositions were prepared by melt mixing, hot-pressed into thin films and their properties tested. The results showed that, although the TPU could toughen the PLL, the blends were immiscible leading to phase separation with the TPU domains distributed in the PLL matrix. However, addition of the PLLCL copolymer could partially compatibilize the blend by improving the interfacial adhesion between the two phases. Biodegradability testing showed that the blends were biodegradable and that the PLLCL copolymer could increase the rate of biodegradation under controlled composting conditions. The 3-component blend of composition PLL/TPU/PLLCL = 90/10/10 parts by weight was found to exhibit the best all-round properties.